Environmental Seasonality Affects the Growth, Yield and Economic Viability of Irrigated Forage Species in Dry Regions - dos Santos, Agda Raiany Mota; de Morais, José Edson Florentino; Salvador, Kaique Renan da Silva; de Souza, Carlos André Alves; Araújo Júnior, George do Nascimento; Alves, Cleber Pereira; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; da Silva, Marcelo José; de Carvalho, Franciê Gomes; dos Santos, Ashlei Shaina Lopes; dos Santos, Wilma Roberta; Campos, Fleming Sena; et al. (Wiley, 2025)
Irrigation in semi-arid regions overcomes edaphoclimatic limitations, guaranteeing livestock farming and reducing the seasonality of forage production. The objective is therefore to evaluate the influence of seasonal variations on the development and accumulation of forage species. The study was conducted in the semi-arid region of Brazil over several harvests from 2020 to 2023 in a randomized block design with four replications, comprising pasture grasses (Brachiaria, buffel, Mombasa and Tanzania), silage crops (BRS Capiaçu, elephant grass, maize and sorghum) and protein sources (alfalfa, Gliricidia, Leucaena and Moringa) subjected to a fixed irrigation regime based on 100% reference evapotranspiration. Tanzania, BRS Capiaçu and Leucaena presented relatively high dry matter yields of 27.0, 111.3 and 36.2 Mg ha−1, respectively. The buffelgrass–sorghum–pigeonpea intercropping system was more efficient in terms of dry matter production (44.5 Mg ha−1). The economic viability varied greatly between cycles and seasons, with sorghum, BRS Capiaçu and Gliricidia standing out as having a positive benefit–cost ratio during all the cycles evaluated. This study reveals how environmental changes affect the development and yield of forage crops, providing insights for productive and economic sustainability in semi-arid regions with the use of irrigation.
Keywords: economic viability; forage performance; intercropping system; irrigation; semi-arid regions; sustainability